Analisis Usability Pada Aplikasi Momby Spa Menggunakan Metode Usability Testing - Hilmy Farid; Dadang Yusup; Carudin Carudin (Peneliti.net, 2022)
Momby Spa is an application that offers baby health therapist services that aim to bridge the gap between therapists and users. However, the Momby Spa application is still less attractive to the public. This is evident from the total number of downloads in the play store which is only hundreds of downloads. Therefore, it is necessary to conduct a usability analysis which includes aspects of effectiveness, efficiency, and user satisfaction to determine the level of usability. This study uses the usability Testing method with the target of Testing 20 mothers who have toddlers and have never used the Momby Spa application. As a result, the level of effectiveness of the Momby Spa application has a value of 95%, the level of user efficiency in finding information is 0.0644 goals/sec and the level of user satisfaction is marginal and ranks C. This shows that the usability level of the Momby Spa application is still has a usability level that is quite acceptable to users because it has a high level of effectiveness and has sufficient user satisfaction.